The Constitutional Prism of Louis-Philippe Pigeon and Jean Beetz - Conklin, William (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1989)
After introducing the concept of an "image of a constitution", Mr Conklin examines the federalism writings and judgments of Justices Pigeon and Beetz with a view to identifying the bounderies of their respective concepts of a constitution. He argues that their writings presuppose coherent answers to such boundaries as the role of a text as the primary source of law, the posited character of rules, rules as the starting point of constitutional analysis, the scientistic role of a lawyer, and a horizontal / vertical spectrum of posited rules. Mr. Conklin claims that their understanding of law collapses into a more primordial image of law whose boundaries we have for too long left unexamined.